RONGGENG: KUASA TUBUH PEREMPUAN - Ela Mutiara Waluya (Universitas Lancang Kuning, 2022)
Talking about Ronggeng is talking about women, bodies, and stage. Body with reality, stage with social. Discourse about female dancers in performances is conditioned by the limits of understanding the female body figure itself. Colonialism has shifted the function, meaning, and form of Ronggeng's performances. This event represents that the female body as an object that can be repressed as well as enjoyed, regulated, and asked to be free, is like a dualism of opposite perspectives. Ronggeng's discourse as a ritual body occupies the highest position which is shaded by the birth of social construction. The view of sensuality places the Ronggeng dancer from subject to object, then objectifies the physical form of a woman's body. This study uses a qualitative method with a constructivist paradigm approach, where the truth of social reality is seen as a result of social construction. The truth of social reality is relative/compound and has different meanings for each person. This study aims to find the position of women in power relations by looking at the structure of the Ronggeng performance.